The dare : a novel - Kara, Lesley (Ballantine Books, 2021)
"She thought she had put the questions to rest. But someone from her past wants answers. From the bestselling author of The Rumor and Who Did You Tell? comes an electrifying new novel of suspense. At the time it was exciting. A game of dare, but one that had motive and justification. Children can be so judgmental, can't they? I can still hear her cry as she toppled forwards, the dull thud of her body as it landed on the pavement. Lizzie and Alice are the best of friends, as close as can be. Until one day when they're out playing by the train tracks, and a childish spat triggers Lizzie's epilepsy. When she comes to, she finds an unimaginable horror: Alice has been killed. Lizzie is devastated, and as she tries to cope with her grief, she is shocked to find herself alienated from Alice's friends and relatives, who are convinced she somehow had a role in her friend's death. I knew that whatever she wanted me to do, I'd do it. Like that first, dreadful dare. Years later, Lizzie has tried to move on. She's engaged to a wonderful man and is starting a new life in London. But someone from her past isn't willing to forgive and forget. They want answers. And they'll do anything to pry them from her. Even if Lizzie doesn't know them herself"--